The relationships between personal resilience and leadership practices of school principals in Jordan - Al-Omari, Aieman Ahmad (Advances in Social Sciences Research Journal, 2017)
The study aimed to investigate the relationships between personal resilience and leadership practices of school principals in Jordan. The sample consisted 800 teachers chosen randomly from Zarqa governorate schools. Two questionnaires: The Personal Resilience Questionnaire, and Leadership Practices Inventory (Observer) were used in this study. Results showed that regarding to LPI the mean of encouraging the heart is higher than all other means, followed by enabling others to act, challenging the process, modeling the way, and inspiring a shared vision. With regard to the seven dimensions of the PRQ Scale, the mean of organized is higher than all other means, followed by flexible: social, flexible: thoughts, proactive, focused, positive: the world, and positive: yourself. Statistically significant, positive relationships were observed among: Positive: The World with challenging the process, inspiring a shared vision, enabling others to act, modeling the Way, and encouraging the heart. Positive: Yourself with challenging the process. Focused with challenging the process, and inspiring a shared vision. Flexible: Thoughts with challenging the process, and inspiring a shared vision. Organized with inspiring a shared vision, and modeling the way. There were no significant differences between BSc. and Graduate teachers in all dimensions of LPI. There were significant differences in LPI overall,the differences were for BSc., there is no difference in teachers perceived the principals personal resilience related to their gender, education, and teaching experience.